2012
DOI: 10.1080/21548455.2011.610134
|View full text |Cite
|
Sign up to set email alerts
|

How Do People Think About the Science They Encounter in Fiction? Undergraduates investigate responses to science inThe Simpsons

Abstract: In this study, students and staff involved in an undergraduate science communication course investigated people's responses to a science-rich episode of the animated sitcom The Simpsons. Using focus groups, we sought to find out if and how the episode influenced our 34 participants' perceptions of science, but our results problematised the very notion of influence. People's responses to the science in the episode varied widely, and sometimes in contradictory ways, from some participants seeing no science at al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(12 citation statements)
references
References 20 publications
0
12
0
Order By: Relevance
“…Here researchers and policy makers have raised concerns that exposure to science in popular culture leads to inaccurate beliefs (Marsh et al, 2003). As an example in 2000 the US National Science Foundation suggested that “fictional media have corroded the public's critical thinking skills and have hindered scientific literacy” (Kirby, 2000, p.262) and in 2010 the President of the Federation of Australian Scientific and Technological Societies stated that Australians' “worrying science literacy levels demonstrates that students have perhaps been learning about science through Jurassic Park instead of through the education system” (quoted in Orthia et al, 2012, p.150). Science in film has come under particular criticism.…”
Section: Science Genetics and Popular Culturementioning
confidence: 99%
“…Here researchers and policy makers have raised concerns that exposure to science in popular culture leads to inaccurate beliefs (Marsh et al, 2003). As an example in 2000 the US National Science Foundation suggested that “fictional media have corroded the public's critical thinking skills and have hindered scientific literacy” (Kirby, 2000, p.262) and in 2010 the President of the Federation of Australian Scientific and Technological Societies stated that Australians' “worrying science literacy levels demonstrates that students have perhaps been learning about science through Jurassic Park instead of through the education system” (quoted in Orthia et al, 2012, p.150). Science in film has come under particular criticism.…”
Section: Science Genetics and Popular Culturementioning
confidence: 99%
“…The rationale is sometimes practical: to explore how fiction can be used as a communication tool, particularly in health promotion which increasingly uses fiction to deliver health messages [Brodie et al, 2001;Davin, 2003;Hether et al, 2008;Howe, Owen-Smith and Richardson, 2002;Levy, 2015;Pelto and Singh, 2010;Smith, Downs and Witte, 2007]. Researchers have also investigated fiction's impact on audience engagement with climate change [Leiserowitz, 2004;Lowe et al, 2006]; genetic research [Donkers and Orthia, 2016;Kitzinger, 2010;Reid, 2012]; gender and science careers [Simis et al, 2015;Steinke et al, 2012]; and science more broadly, including understandings of the nature of science [Jackson, 2013;Li and Orthia, 2013;Li and Orthia, 2016;Myers and Abd-El-Khalick, 2016;Orthia, Dobos et al, 2012]. Some conclude fiction can be effective for imparting scientific information if it is relevant to the audience [e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Levy, 2015;Smith, Downs and Witte, 2007]; it can influence attitudes towards matters like climate change or cloning, but not particularly strongly [Donkers and Orthia, 2016;Leiserowitz, 2004;Lowe et al, 2006;Reid, 2012]; it can sometimes shape characterizations of scientists and might role-model scientist careers, but there is sparse evidence [Li and Orthia, 2016;Simis et al, 2015;Steinke et al, 2012]; and it can sometimes awaken people's interest in science [Jackson, 2013;Li and Orthia, 2013]. Most studies suggest audiences process fictive content critically, fully aware it is fiction, and use it as a discursive resource to enrich discussions about science, rather than absorbing its messages wholesale [Green, 2019;Kitzinger, 2010;Orthia, Dobos et al, 2012]. Consequently, it seems that different people respond to a given text differently.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Hopefully, this trend will be underpinned by research on its effectiveness. Such research is still scarce and fragmented as excellently reviewed by Orthia et al (5), and opens a whole new field for science educators and communicators.…”
Section: Communication and Emotionsmentioning
confidence: 99%